The Development of Waggle Courtier Doll Molding - คงศรีชาย, ณัฐวิทย์; อนันต์วราพงษ์, อมรรัตน์ (Ratchaphruek Journal, 2019)
This study aimed to investigate the customers demand on waggle courtier doll molding, to develop waggle courtier doll molding that answers the customers demand and to evaluated customers’ satisfaction toward the waggle courtier doll molding. The four three-dimensional (3D) pattern of waggle courtier doll molding were designed. The pattern will be evaluated and use in further step. The participants were five technicians who are expert in manufacturing and product design. Research instrument was open-ended questionnaire. Pattern number 1 was selected by the technicians because it was the most suitable pattern for the waggle courtier doll molding. The model of waggle courtier doll molding was made. The product will be used as the sample in customers’ satisfaction evaluation step. The participants were 50 customers who are interesting in waggle courtier doll molding. The research instrument was customers’ satisfaction questionnaire. The highest customers’ satisfaction score in each aspect was 1) product design aspect, the customers satisfied the concordant of material and product ( =4.96) 2) the beauty of product, the consumers are satisfied the delicate and neat of product ( =4.94) 3) the usefulness aspect, the customers satisfied the safe use of product ( =4.70) and 4) the satisfaction toward whole product, the waggle courtier doll molding gained the customer satisfaction in highest level ( =4.76).